Investigating the Effect of Nitrogen and Irrigation on Some Physiological, Quantitative and Qualitative Traits of Greenhouse Tomato - Saeed Mohammadzade; Morteza Goldani; Fatemeh Yaghobi; Mohammad Bannayan Aval (Majallah-i ̒Ulum-i Bāghbānī, 2024)
IntroductionIncreasing the tolerance to drought and nitrogen stress in tomato cultivars is essential for the sustainable and environmentally friendly production of this product. Also, knowing the morpho-physiological, biochemical and molecular responses to drought and nitrogen stress is important for a comprehensive understanding of plant water tolerance mechanisms and nitrogen limitation conditions in higher plants. Therefore, the purpose of this study was to investigate the effect of different levels of irrigation and nitrogen fertilizer on the quantitative and qualitative characteristics of tomatoes in different Cluster rows under greenhouse conditions. Materials and MethodsThe experiment was conducted at the research greenhouse of the Faculty of Agriculture, Ferdowsi University of Mashhad, in two years, 2021-02 and 2022-03. The experiment was set up as split-plot layout based on randomized complete block design with three replications. Irrigation levels were considered as the main plot at three levels: 75% (I75), 100% (I100), and 125% (I125) of the crop water requirement. Nitrogen fertilizer was considered as the subplot at four levels: control (no nitrogen), 75 kg ha-1 (7.5 g m-²), 150 kg ha-1 (15 g m-²), and 225 kg ha-1 (22.5 g m-²) from urea as the nitrogen source. Tomato seeds (Newton cultivar) were sown in polyethylene seedling trays with a coco peat and perlite mixture as the substrate. The seedlings were transplanted to the main field at 15 cm height with 3-4 true leaves. In all stages of growth, consistent agricultural practices were applied, including weed control, pest and disease management. Fertilization for tomato plants was based on soil analysis. Initially, after transplanting the seedlings, a complete fertilizer with high phosphorus (NPK 10-52-10) was applied at a ratio of 1.5 kg per thousand plants. In the subsequent stages, complete fertilizers (NPK 20-20-20) and high-potassium fertilizers (NPK 20-20-36) were applied through irrigation. Throughout the plant's growth stages, to prevent potential deficiencies and harm to growth and fruit development, micronutrients were applied as foliar sprays. Results and Discussion The results for all three Clusters showed that although nitrate accumulation was higher in the first year compared to the second year, in both years, nitrate accumulation was higher at I75 and 225 kg ha-1 nitrogen compared to the other treatments. The highest nitrate accumulation in the sixth (6.12 mg.kg-1) and seventh (6.29 mg.kg-1) Clusters was observed in I75 and 225 kg ha-1 nitrogen treatment in the first year. In the eighth Cluster, contrary to the sixth and seventh Clusters, the highest nitrate accumulation was obtained in I100 and 225 kg/ha nitrogen (6.43 mg.kg-1) in the first year. Chlorophyll decreased with stress but increased with nitrogen levels. In all four Clusters, the highest chlorophyll a content was obtained in I100 and 225 kg ha-1 nitrogen, with values of 3.75, 3.70, 3.30, and 3.85 mg g-1 fresh weight, respectively. The highest fruit number per square meter was obtained in I125 and 225 kg ha-1 nitrogen treatment in the second year (260 fruits), although there was no significant difference compared to the first year. Furthermore, this treatment produced 11% more fruits than the highest fruit number at 100% moisture. The highest single fruit weight was obtained in I125 and 225 kg ha-1 nitrogen treatment in the first year of the experiment (254 g), although there was no significant difference compared to the second year. Additionally, this treatment showed no significant difference in fruit weight compared to the 225 kg ha-1 nitrogen and I100 treatment in the first year but was 11% higher in the second year. The highest yield (65.1 kg m-²) was obtained at I125 and 225 kg ha-1 nitrogen. However, in the control treatment without fertilizer, there was no significant difference in yield at I100 and I125. Furthermore, the highest water use efficiency was observed at I100, followed by I75. In all fertilizer treatments, I125 treatment had the lowest water use efficiency. The highest water use efficiency (285 kg m-³) was obtained at I100 and 225 kg ha-1 nitrogen. Conclusion In general, the results demonstrated that while excessive nitrogen fertilizer increased nitrate accumulation at different irrigation levels, the increased use of irrigation water reduced nitrate accumulation in tomato fruits while improved yield. Moreover, no significant difference in fruit yield was observed between I125 and I100, but optimum yield and favorable water use efficiency were obtained with less water consumption. Based on the results of this experiment, the recommended treatment under greenhouse conditions is irrigation at 100% of the FC and the use of 250 kg ha-1 nitrogen.